Hamstring muscle fibre typology is not associated with hamstring strain injury history or performance in amateur male soccer players: a retrospective magnetic resonance spectroscopy study - Schuermans, Joke; Witvrouw, Erik; Wezenbeek, Evi; Lievens, Eline (Biology of Sport, 2023)
Hamstring strain injuries (HSI) are still the most common injuries in soccer. Recent research has been focusing on the role of hamstring muscle morphology and architecture. The hamstring’s fibre type composition might play a role as well, but this has never been investigated in the light of HSI risk in an athletic population. The purpose of this study was to investigate the association between hamstring muscle fibre type, hamstring strain injury history (HSIH), performance and isokinetic strength in a population of amateur male soccer players. In this cross-sectional observational study, 44 male soccer players (22 with and 22 without HSIH) participated. The research consisted of a non-invasive fibre composition evaluation using proton magnetic resonance spectroscopy ( 1 H-MRS), functional performance (evaluated by means of maximal jumping height, maximal sprinting speed and hamstring muscle strength endurance (single leg hamstring bridge testing)), and isokinetic strength testing. The results revealed that hamstring carnosine concentration demonstrated a high inter-individual variability within this soccer population and was not significantly associated with either HSIH or with any of the functional performance parameters. The only secondary outcome measure presenting a significant association with the intramuscular carnosine content was the hamstrings’ explosive strength production capacity, objectified by means of the time to peak torque (TPT), measured concentrically at an angular velocity of 240 degrees/second (°/s) during isokinetic strength testing. This TPT was significantly shorter in players presenting higher carnosine concentrations (p = 0.044). The findings indicate that in male amateur soccer players (1) the hamstrings have no distinct fibre type dominance and (2) fibre typology in this population does not relate to HSIH or performance.